The seasonal haulout cycle of the declining southern elephant seal, Mirounga Leonina, population at Marion Island - Bester, Marthan Nieuwoudt (University of Pretoria, 2013)
Dissertation (MSc (Zoology))--University of Pretoria, 2006.